The Influence of Time Pressure and Promotional Pricing in Tiktok Live Streaming on Impulse Buying Among Generation Z - Cheryssa Felesia Lais (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Sabda Setia, 2026)
This study investigates the influence of time pressure and promotional pricing in TikTok live streaming on impulse buying among Generation Z, employing the Stimulus-Organism-Response (S-O-R) framework. The rapid growth of e-commerce and TikTok live streaming has increased impulsive buying behavior among Gen Z consumers, making it important to understand the factors driving such behavior in digital commerce. A quantitative method was utilized, with data collected through an online questionnaire distributed to 232 Gen Z respondents who had previously made purchases via TikTok live streaming. The results indicate that all independent variables collectively influence impulse buying. Both time pressure and promotional pricing significantly affect perceived enjoyment and directly impact impulse buying. Moreover, perceived enjoyment is found to mediate these relationships. The standardized beta coefficient for time pressure is 0.383, while promotional pricing has a coefficient of 0.337, both showing indirect effects through increased perceived enjoyment. These findings highlight the effectiveness of limited-time offers and attractive pricing strategies in stimulating impulse buying behavior among Gen Z consumers on TikTok Live.